2008
DOI: 10.1158/0008-5472.can-07-1597
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH3 Signaling Pathway Plays Crucial Roles in the Proliferation of ErbB2-Negative Human Breast Cancer Cells

Abstract: ErbB2-negative breast tumors represent a significant therapeutic hurdle because of a lack of effective molecular targets. Although NOTCH proteins are known to be involved in mammary tumorigenesis, the functional significance of these proteins in ErbB2-negative breast tumors is not clear. In the present study, we examined the expression of activated NOTCH receptors in human breast cancer cell lines, including ErbB2-negative and ErbB2-positive cell lines. Activated NOTCH1 and NOTCH3 proteins generated by ;-secre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
126
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(144 citation statements)
references
References 33 publications
15
126
1
2
Order By: Relevance
“…The MDA-MB-231 line expresses Notch 1 and Notch 4. The MDA-MB-468 line expresses Notch 1 (Stylianou et al, 2006) and Notch 3 (Yamaguchi et al, 2008). The MCF-7 line expresses Notch 1 (Stylianou et al, 2006;Rizzo et al, 2008), Notch 3 (Yamaguchi et al, 2008) and Notch 4 (Sun et al, 2005).…”
Section: Notch 3 Dependency Of Ibc Embolus Y Xiao Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…The MDA-MB-231 line expresses Notch 1 and Notch 4. The MDA-MB-468 line expresses Notch 1 (Stylianou et al, 2006) and Notch 3 (Yamaguchi et al, 2008). The MCF-7 line expresses Notch 1 (Stylianou et al, 2006;Rizzo et al, 2008), Notch 3 (Yamaguchi et al, 2008) and Notch 4 (Sun et al, 2005).…”
Section: Notch 3 Dependency Of Ibc Embolus Y Xiao Et Almentioning
confidence: 99%
“…It could be argued, however, that the stem cell-like properties of Notch 3 signaling and ALDH positivity exhibited by MARY-X (as it is triple negative) could be a manifestation of its basal origin rather than its IBC origin (Bertucci et al, 2006;Stylianou et al, 2006;Yamaguchi et al, 2008;Sansone et al, 2007a, b). IBC is a heterogeneous disease and it has been reported that the same molecular subtypes present in non-IBC are also present in IBC (Bertucci et al, 2005).…”
Section: Notch 3 Dependency Of Ibc Embolus Y Xiao Et Almentioning
confidence: 99%
“…The enhanced and independent cell proliferation is an essential step in tumor metastasis [5] . Recent studies show that the signal transduction pathways, such as NOTCH3-mediated signaling, ErbB-mediated cascade, serum and glucocorticoid-inducible kinase (SGK)-mediated signaling, G proteincoupled receptor GPR40-mediated signaling and ERK/MAPK signaling, are involved in the regulation of breast cancer cell proliferation [6][7][8] . It has been reported that Wnt signaling plays an important role in regulation of cell proliferation in several cancers, such as prostate cancer, lung cancer, myeloma and www.chinaphar.com Zhou XL et al Acta Pharmacologica Sinica npg colon cancer [9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…By providing an internally hydrophilic environment within the plasma membrane (Lazarov et al, 2006), g-secretase is responsible for cleaving more than 30 substrates, including amyloid precursor protein (APP), Notch (Mumm et al, 2000), ErbB4 (Ni et al, 2001), E-cadherin (Marambaud et al, 2002), CD44 (Lammich et al, 2002) and p75 (Schluesener et al, 1992), which regulate vital cell functions such as proliferation, cell cycle, cell adhesion and apoptosis. Interestingly, increased expression of Notch ligands, receptors, and/or downstream targets are highly associated in the pathogenesis of breast (Jones et al, 2004;Stylianou et al, 2006;Yamaguchi et al, 2008), brain (Purow et al, 2005), colon (Akiyoshi et al, 2008), cervical (Liu et al, 2007) pancreatic (Doucas et al, 2008) and skin cancers (Dang et al, 2006). Thus, the g-secretase complex may be a potential therapeutic target in a wide array of carcinomas.…”
mentioning
confidence: 99%
“…In addition, Numb, a negative regulator of Notch signalling (McGill and McGlade, 2003), is significantly reduced in 50% of breast cancer tissues, inversely correlating with tumour size (Pece et al, 2004) and correlating with a poor prognosis (Colaluca et al, 2008). Inhibiting Notch signalling by overexpression of Numb reverts the transformed phenotype of MCF-7 cells (Stylianou et al, 2006), whereas silencing of Notch 3 inhibits proliferation and promotes apoptosis in ErbB2-negative breast cancer cell lines (Yamaguchi et al, 2008). Moreover, overexpression of Notch in non-tumourigenic breast epithelial cells induces transformation in vitro (Imatani and Callahan, 2000;Stylianou et al, 2006).…”
mentioning
confidence: 99%